2014
DOI: 10.1161/circep.113.001217
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Programming Strategies Aimed at Reducing Nonessential Implantable Cardioverter Defibrillator Therapies on Mortality

Abstract: Background-Patients who receive implantable cardioverter defibrillator therapies are at higher risk of death versus those who do not. Programmed settings to reduce nonessential implantable cardioverter defibrillator therapies (therapy reduction programming) have been developed but may have adverse effects. This systematic review and meta-analysis assessed the relationship between therapy reduction programming with the risks of death from any cause, implantable cardioverter defibrillator shocks, and syncope. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(62 citation statements)
references
References 37 publications
(14 reference statements)
1
55
1
5
Order By: Relevance
“…Syncopal episodes related to arrhythmic events and deaths were similar between the 2 groups.Following shortly on the heels of these trials, 2 meta-analyses including the above studies were published in 2014. Tan et al presented the data from the RELE-VANT, PREPARE, MADIT-RIT, ADVANCE III, PROVIDE, and EMPIRIC trials [100,101]. A 30% reduction in the risk of death was found in the therapy reduction group when including all 6 studies; however, similar results were observed when separately considering the 4 randomized trials and the 2 observational studies.…”
Section: Duration Criteria For the Detection Of Ventricular Arrhythmiamentioning
confidence: 86%
“…Syncopal episodes related to arrhythmic events and deaths were similar between the 2 groups.Following shortly on the heels of these trials, 2 meta-analyses including the above studies were published in 2014. Tan et al presented the data from the RELE-VANT, PREPARE, MADIT-RIT, ADVANCE III, PROVIDE, and EMPIRIC trials [100,101]. A 30% reduction in the risk of death was found in the therapy reduction group when including all 6 studies; however, similar results were observed when separately considering the 4 randomized trials and the 2 observational studies.…”
Section: Duration Criteria For the Detection Of Ventricular Arrhythmiamentioning
confidence: 86%
“…However, shock therapies have been reported to be associated with pain, depression, proarrhythmia, and increased risk of all-cause mortality [4][5][6][7]. Several trials demonstrated that a long detection window and a high-rate cutoff reduced ICD therapies in primary prevention (PP) patients [8][9][10][11][12]. As for secondary prevention (SP) patients, only one subanalysis of the ADVANCE III randomized clinical trial reported that the ICD setting that combined a long detection window for ventricular tachyarrhythmias ≤320 ms with antitachycardia pacing (ATP) during charge reduced overall ICD therapies in SP patients [13].…”
Section: Introductionmentioning
confidence: 99%
“…Optimal programming aiming at reducing inappropriate or unnecessary shocks may provide up to a 30% relative decrease in mortality with no apparent increase in the risk of syncope[31]. During a VTS, ICD programming focuses on minimizing the frequency of shocks.…”
Section: Resultsmentioning
confidence: 99%